Selected Abstracts of the 14th International Workshop on Neonatology; Cagliari (Italy); October 24th-27th, 2018 - Various Authors, — (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2018)
Selected Abstracts of the 14th International Workshop on Neonatology; Cagliari (Italy); October 24th-27th, 2018 • THE REVOLUTION OF MICROBIOMICS • NUTRITION, BACTERIA AND PROBIOTICS IN PERINATAL AND PEDIATRIC HEALTH ABS 1. AWARENESS ABOUT LABIA MINORA FUSION AMONG LEBANESE PEDIATRICIANS • M. Amm, M.C. Fadous Khalife, V. Modica, H. Feghali, J. Mardini, M. AlOjaimi ABS 2. SUCCESSFUL CONSERVATIVE MANAGEMENT OF A GIANT UNILATERAL PNEUMATOCELE IN AN EXTREMELY LOW BIRTH WEIGHT INFANT • F. Bissolo, C. Forcellini, R. Beghini, S. Lauriola, M. Ventola, B. Ficial, E. Bonafiglia, L. Chini, L. Pecoraro, I. Sibona, R. Frassoldati, P. Biban ABS 3. METABOLOMICS IN NEWBORNS WITH INTRAUTERINE GROWTH RESTRICTION: EFFECTS OF MATERNAL SMOKING • L. Corona, F. Cesare Marincola, S. Corbu, R. Pintus, V. Fanos, A. Dessì ABS 4. THE C.O.R.E. STUDY: IMPACT ON HOSPITAL READMISSION RATES OF A NEW PROTOCOL FOR THE ANALYSIS OF CARDIORESPIRATORY STABILITY IN PRETERM INFANTS BEFORE NICU DISCHARGE • F. Cresi, E. Cocchi, A. Pirra, F. Logrippo, C. Plazzotta, D. Enrietti, R. Bagna, E. Maggiora, V.A. Dell’Anna, E. Bertino ABS 5. FOLINIC ACID TREATMENT IN KEARNS-SAYRE SYNDROME (KSS): CURRENT APPROACH • M. Limone, M. Rossano, F. Guerra, E. Flore, M. Balzarini, L. Boccone, M. Marica, P. Moi ABS 6. SIBLING CLUSTERING OF VITAMIN D STATUS IN CHILDREN FROM NORTHERN SARDINIA • M.G. Clemente, D. Argiolas, L. Argiolas, G. Sotgiu, R. Antonucci ABS 7. COMPARISON EFFECTS OF HOLDER PASTEURIZATION AND HIGH-TEMPERATURE SHORT-TIME PASTEURIZATION ON ANTIVIRAL ACTIVITY OF HUMAN MILK • M. Donalisio, M. Rittà, R. Francese, A. Civra, P. Tonetto, A. Coscia, M. Giribaldi, L. Cavallarin, G.E. Moro, S. Sottemano, D. Lembo, E. Bertino ABS 8. ULTRASOUND-GUIDED PERCUTANEOUS CENTRAL VEIN CANNULATION IN NEONATES • F. Piersigilli, I. Savarese, F. Campi, I. Bersani, S. Sgrò, A. Dotta ABS 9. BECKWITH WIEDEMANN SYNDROME: AN INTERESTING CASE REPORT • A. Satta, R. Murru, G. Senes, V. Fanos, G. Faa, M.L. Lai ABS 10. SPINAL MUSCULAR ATROPHY: A NEW COMPASSIONATE OR THERAPEUTIC PERSPECTIVE? • S. Vendemmia, G. Parisi, N. Vendemmia, M. Vendemmia ABS 11. MOTHERS AND ADDICTION: AN EXPLORATIVE STUDY IN NEONATOLOGY • G.M. Rossi, C. Cacciatore, R. Pintus, A. Dessì ABS 12. OLFACTORY PERCEPTION AND OLFACTORY EVENT-RELATED POTENTIALS IN NEWBORNS WITH 3M SYNDROME • S. Invitto, A. Grasso, V. de Pascalis, R. Marulli, G. Trianni, A. Paladini, P. Paladini ABS 13. MYCOSIS FUNGOIDES IN A 9-YEAR-OLD GIRL. A CASE REPORT • V. Aimola, G. Cerrone, E. Robustelli, C. Ferreli, F. Rongioletti, G. Faa, L. Pilloni ABS 14. EXPLORING NEW INSIGHTS INTO AUTOIMMUNE HEPATITIS PATHOGENESIS: DESCRIPTION OF TWO CASES • R. Frassetto, A. Cambiganu, N. Vacca, R. Antonucci, M.G. Clemente ABS 15. BREASTFEEDING AND THE USE OF LATCH SCORE: FIRST DATA FROM A GROUP OF 50 MOTHERS • G. Corongiu, R. Pintus, M. Zonza, A. Dessì ABS 16. HYPERGLYCEMIA IN A NEWBORN: BERARDINELLI-SEIP CONGENITAL LIPODYSTROPHY • G. Nicolas, V. Modica, J. Sakkal, M.C. Khalife ABS 17. PLACENTA IN DOWN’S SYNDROME: DIFFERENCES IN CYTOTROPHOBLAST AND SYNCYTIOTROPHOBLAST MATURATION • V. Vallascas, D. Fanni, G. Senes, R. Murru, F. Cau, G. Gerosa ABS 18. METABOLOMICS, IRON, AND PREVENTION OF THE ANAEMIA OF PREMATURITY • G. Ledda, M. Puddu, F. Cesare Marincola, S. Corbu, R. Pintus, E. Coni, V. Fanos, A. Dessì ABS 19. VALIDATION OF HEEL STICK MICROSAMPLING TO OPTIMIZE MICAFUNGIN DOSES IN NEONATES • I. Bersani, C. Auriti, M.P. Ronchetti, B.M. Goffredo, F. Piersigilli, S. Cairoli, A. Dotta, M.P. Pai ABS 20. HEPATOCYTES IN WILSON’S DISEASE: A SCANNING ELECTRON MICROSCOPY INVESTIGATION • T. Congiu, C. Gerosa, D. Fanni, F. Cau, M. Piras, G. Faa ABS 21. FUSOBACTERIUM NUCLEATUM IN CHILDREN’S ORAL CAVITY. A COMMENSAL-TURNED PATHOGEN THAT INCREASED RADICALLY IN 5,000 YEARS • M.P. Contu, E. Casula, O. Fonzo, G. Paglietti, E. Usai, G. Denotti, V. Garau, R. Martorelli, F. Coghe, G. Orrù ABS 22. EFFECTS OF A PSYCHOLOGICAL FOLLOW-UP ON CARE OF CHILDREN AND ADOLESCENTS FURTHER TO ACCESS TO PEDIATRIC EMERGENCY ROOM FOR PSYCHOLOGICAL PROBLEMS • A. Carollo, C. Polizzi, G. Perricone ABS 23. METABOLOMIC ANALYSIS IN PATIENTS WITH BICUSPID ARTIC VALVE DISEASE, WITH OR WITHOUT AORTIC DILATION: TOWARDS A TAILORED TREATMENT • M. Meli, A. Dessì, F. Cesare Marincola, E. Conforti, R. Pintus, S. Corbu, V. Fanos, M. Chessa ABS 24. ROLE OF ELECTRON MICROSCOPY IN THE STUDY OF HEPATIC IRON OVERLOAD • M. Piras, T. Congiu, D. Fanni, C. Gerosa, F. Cau, G. Faa ABS 25. ATOPIC DERMATITIS: GOOD NEWS BY SKIN MICROBIOME • N. Maiello, S. Vendemmia, A.M. Basilicata ABS 26. TEMPORAL VARIABILITY OF URINARY METABOLOME IN PRETERM NEWBORNS WITH NECROTIZING ENTEROCOLITIS • F. Giardina, A. Dessì, A. De Magistris, F. Cesare Marincola, S. Corbu, R. Pintus, V. Fanos, J-C. Picaud ABS 27. AN INNOVATIVE INTEGRATED WORKING MODEL FOR THE ACCOMPANIMENT AND PSYCHOLOGICAL SUPPORT TO WOMEN/COUPLES WITH AT RISK PREGNANCY OR BIRTH IN THE MATERNAL INFANT DEPARTMENT • M.V. Rizzo, S. Marotta, V. Cavarretta, G. Perricone ABS 28. HYPOTHERMIC TREATMENT IN NEONATES WITH HYPOXIC-ISCHEMIC ENCEPHALOPATHY: A 5 YEARS EXPERIENCE STUDY • S. Salomè, M. Morelli, G. Mansi, A. Romano, M. Vendemmia, F. Raimondi ABS 29. AUTOIMMUNE HEPATITIS AND AUTOIMMUNE CHOLANGITIS WITH FULMINANT CLINICAL COURSE IN A YOUNG GIRL: A CASE REPORT • C. Rossi, D. Fanni, G. Cerrone, C. Gerosa, A. Ravarino, F. Coghe, Y. Gibo, G. Faa ABS 30. PULMONARY HYPERTENSION IN A LATE PRETERM: A CASE REPORT • G. Cerrone, V. Aimola, C. Loddo, F. Cau, G. Faa, C. Gerosa ABS 31. AUDITING PEDIATRIC EMERGENCIES IN LEBANON • M. Amm, Z. Ghorayeb, V. Modica, G. Nicolas, H. Feghali, M. AlOjaimi, M.C. Fadous Khalife ABS 32. OCT-4 EXPRESSION IN THE HUMAN FETAL OVARY DURING GESTATION • F. Cau, C. Gerosa, M.L. Pinna, G. Senes, F. Ronchi, C. Botta ABS 33. VERY LOW BIRTH WEIGHT AND LONG-TERM OUTCOMES: A 14 YEARS EXPERIENCE IN THE NICU OF A.O.U. FEDERICO II IN NAPLES • M. Vendemmia, G. Mansi, A. Romano, S. Salomè, A. Romano, F. Diana, F. Raimondi ABS 34. IF IT IS NOT A COMMON HEADACHE? ARACHNOID CYST WITH CRONIC SUBDURAL HEMATOMA POST MINOR HEAD TRAUMA IN CHILD • F. Mecarini, M. Tiddia, G. Cherchi, M.L. Giua Marassi, B. Biancu, P.F. Cappai, A. Medda, A. Canetto ABS 35. ADVANCED MAGNETIC RESONANCE IMAGING IN PEDIATRIC MUSCLE DISEASES • M. Marras, G. Vivanet, A. Lai ABS 36. ACTION – AGGRESSION IN CHILDREN: UNRAVELING GENE-ENVIRONMENT INTERPLAY TO INFORM TREATMENT AND INTERVENTION STRATEGIES • M. Mauri; ACTION CONSORTIUM ABS 37. INTUSSUSCEPTION IN A PREMATURE NEONATE: A RARE AND OFTEN MISDIAGNOSED CLINICAL ENTITY • L. Giua Marassi, D. Panico, F. Puddu, L. Mascia, M. Puddu ABS 38. EPSTEIN-BARR VIRUS IN 5 PEDIATRIC PATIENTS WITH HODGKIN’S LYMPHOMA • J.A. Zanda, C. Gerosa, G. Senes, R. Murru, G. La Nasa, G. Faa, D. Fanni ABS 39. UBALDO DIMITA AND THE HUMANIZATION OF CURES IN NEONATOLOGY • L. Cataldi ABS 40. CAN DIFFERENT VENTILATORY APPROACH REDUCE ATELECTASIS ANESTHESIA-INDUCED IN CHILDREN UNDERGOING GENERAL ANESTHESIA DURING MAGNETIC RESONANCE IMAGING? • M. Marras, A. Bullegas, A. Lai ABS 41. TISSUE OXYGENATION AND SPONTANEOUS CLOSURE OF PERIMEMBRANOUS VENTRICULAR SEPTAL DEFECTS • P.P. Bassareo, R. Savage, E. Doran, C. O’Neill, K. Walsh ABS 42. WHAT CAN HIDE A PLEURAL EFFUSION IN A CHILD? THORACIC MASS IN A DRAVET SYNDROME • F. Mecarini, G. Colucci, G. Melis, V. Relli, S. Corda, M.S. Galassi, S. Marras, A. Canetto ABS 43. MATERNITY BLUES: A RISK FACTOR FOR ANHEDONIA, ANXIETY, AND DEPRESSION COMPONENTS OF EDINBURGH POSTNATAL DEPRESSION SCALE • V. Manghina, F. Volpe, L. Giliberti, R. Maione, G. Straface, V. Zanardo ABS 44. OXYGEN THERAPY IN INFANTS WITH EXTREME PERIODIC BREATHING • L. Nosetti, A.C. Niespolo, M. Vergani, A. Salvatoni, M. Agosti ABS 45. A NEWBORN WITH RDS AND CONGENITAL HYPOTHYROIDISM: A CASE REPORT • F. Marino, L. Bertasi, F. Rimondi, F. Rigon, G. Passarella, M. Berard, C. Lorenzetto, S. Rugolotto ABS 46. THE HYPOTHERMIC TREATMENT: A GOOD CHOICE FOR THE BRAIN. WHAT ABOUT THE HEART? • C. Loddo, D. Manus, C. Fanni, G. Palmas, P. Neroni ABS 47. CAPICE: CHILDHOOD AND ADOLESCENCE PSYCHOPATHOLOGY: UNRAVELLING THE COMPLEX ETIOLOGY BY A LARGE INTERDISCIPLINARY COLLABORATION IN EUROPE • H.S.R. Rajula, A.G. Allegrini, E. Shahid, K. Agarwal, V. Karhunen, O. Akingbuwa, E. Haan, E. Diemer, L. Schellhas, A. Thompson, S. Doering, M. Leone, V. Fanos ABS 48. NEONATAL PARECHOVIRUS SEPSIS: A CASE REPORT • F. Marino, L. Bertasi, F. Rimondi, F. Rigon, G. Passarella, M. Berardi, C. Lorenzetto, S. Rugolotto ABS 49. JOURNEY OF FIRST YEAR OF MY Ph.D. AT UNIVERSITY OF CAGLIARI • H.S.R. Rajula, M. Mauri ABS 50. NEONATAL TRANSPORT SERVICE IN SARDINIA: STATE OF THE ART • C. Loddo, M. Puddu, G. Ottonello, C. Fanni, A. Atzei ABS 51. AUTOSOMAL RECESSIVE WAARDENBURG SYNDROME TYPE IV B IN A NEWBORN WITH NEPHRO-UROLOGIC MALFORMATIONS AND INTESTINAL AGANGLIOSIS • D. Milani, C. Marchetti, A. Mussari, R. Mattei, C. Marcellino, C. Scalamogna, S. Rugolotto ABS 52. NEWBORNS IDENTIFICATION PROTOCOL IN NEONATAL INTENSIVE CARE UNITS • A. Casanova, S. Barra, L. Barberini, M. Puddu, V. Fanos ABS 53. HE HAS PAIN, BUT IT IS A GREEN CODE, HE HAS TO WAIT! • Y. Khayamian, M. Manni, M. Mistretta, A. Canetto ABS 54. THE TRAP OF DIGITAL ERA FOR YOUNG MOTHERS • A. Ciubara, M. Burlea, M. Vendemmia, S. Vendemmia ABS 55. PLACENTAL AND FETAL MEMBRANES INFECTION IN PREGNANCY WITH RUPTURE OF MEMBRANES. A PILOT STUDY • S. Cireddu, C. Gerosa, M. Anardu, M. Russo, F. Coghe, V. Fanos, G. Faa, S. Angioni ABS 56. A SYSTEMATIC REVIEW ON THE IMPACT OF THE CONCOMITANT USE OF CANNABINOIDS ON TREATMENT RESISTANCE TO ANTIPSYCHOTICS: A PATHWAY TOWARD AGGRESSION? • M. Pinna, R. Agabio, B. Carpiniello, F. Pinna, V. Fanos, E. Denovan-Wright, M. Manchia ABS 57. EMOTIONAL AND PSYCHOLOGICAL ASPECTS IN LONG-TERM HOSPITALIZED PREGNANT WOMEN • M. Costa, I. Melis, E. Corvetto, C. Giuliani, M. Agus, S. Angioni ABS 58. AN INCESSANT… HEARTTHROB • F. Bardanzellu, I. Bo, M. Puddu, D. Manus, F. Cioglia, A. Atzei, P. Neroni ABS 59. PSYCHOLOGICAL IMPACT OF MISCARRIAGE • G. Impera, F. Dessolis, D. Deiana, M.G. Orlando, C. Giuliani, M. Agus, I. Melis, S. Angioni ABS 60. HUMAN BREAST MILK-ACQUIRED CYTOMEGALOVIRUS INFECTION • F. Bardanzellu, A. Reali ABS 61. ECTROMELIA APPEARANCES • C. Perna, C.D. Arru, C. Porcu, G. Ledda, L. Saba ABS 62. ETIOPATHOGENIC, DIAGNOSTIC AND THERAPEUTIC PARTICULARITIES IN CORROSIVE ESOPHAGITIS IN CHILDREN IN ROMANIA • M. Burlea ABS 63. DOUBLE BLADDER IN AN INFANT? • C.D. Arru, C. Porcu, N. Pandolfo, M. Erta, F. Loi, G. Ledda, G. Ottonello, L. Saba ABS 64. NEONATAL TSH SCREENING VALUE FOR CONGENITAL HYPOTHYROIDISM RELATED TO PFASs AREAS OF VENETO REGION IN NORTH OF ITALY • S. Lauriola, M. Clemente, O. Pepaj, R. Gaudino, P. Cavarzere, F. Antoniazzi ABS 65. THE AETIOLOGY OF MOLAR INCISOR HYPOMINERALIZATION IN PERINATAL AGE: FOCUS ON BREASTFEEDING • F. Cosimi, G. Rosati, F. Fabiano, M. Oricchio, C. Pala, M. Aprile ABS 66. NASAL SEPTAL CHONDRITIS IN AN IMMUNOSUPPRESSED CHILD: RADIOLOGICAL IMAGING AND CLINICAL MANAGEMENT • G. Columbano, F. Carta, M. Porcu, R. Puxeddu, L. Saba ABS 67. CEREBELLAR HYPOPLASIA IN A TERM BABY • C.D. Arru, C. Perna, C. Porcu, M. Puddu, L. Saba ABS 68. NEW DEVICES AND POSSIBLE REALITIES IN THE SHAPING OF THE PRESENT AND THE FUTURE • A. Cuttano, B. Gigantesco, M. Del Pistoia, F. Lorenzoni, P. Ghirri, E. Sigali, S. Bardelli, A. Mattiola, S. Tognarelli, M. Ciantelli, R. Scaramuzzo ABS 69. OSTEOPENIA OF PREMATURITY: AN UNDERESTIMATED DIAGNOSIS • P. Abou Jaude, V. Modica, M. Samarani, G. Nicolas, M. Amm, M.C. Fadous Khalife ABS 70. URINARY METABOLOMICS IN EXTREMELY LOW GESTATIONAL AGE NEWBORN INFANTS AND NEUROLOGICAL OUTCOME AT 2 YEARS: A PRELIMINARY STUDY • C. Fanni, H. Hagberg, M. Alkmark, F. Cesare Marincola, S. Corbu, M.A. Marcialis, M. Testa, M.C. Pintus, C. Loddo, V. Fanos, K. Sävman, V. Fellman